Cardiac magnetic resonance T1 mapping. Part 1: Aspects of acquisition and evaluation. Issue 109 (December 2018) - Reiter, Gert; Reiter, Clemens; Kräuter, Corina; Fuchsjäger, Michael; Reiter, Ursula
Graphical abstract: Highlights: Myocardial T1 mapping techniques are continuously evolving. T1 and ECV estimates depend on acquisition techniques and evaluation strategies. T1 and ECV normal values are spread across wide ranges. z-scores are suggested to report T1 and ECV alterations. Myocardial T1 stress reactivity emerges as new metrics for detection of ischemia. Abstract: While an enormous number of studies have documented pathological alterations of the myocardial native longitudinal relaxation time (T1) and the fraction of the extracellular myocardial volume (ECV), it has also become clear that continuously evolving T1 mapping sequence, acquisition and evaluation techniques have a substantial impact on quantitative results, making the translation of reported findings into routine clinical use particularly challenging. To provide a basis for the discussion of pathological myocardial T1 and ECV alterations, the present review aims to summarize the methodological aspects of myocardial T1 mapping along with technical and physiological factors influencing results and normal ranges of myocardial native T1 and ECV reported across studies.